Enhancing nanofertilizers’ performance for improved yield and quality of cotton - Kanjana, D; Annie, S J; Usharani, S (Plant Science Today, 2025)
Nanofertilizers have shown promise in enhancing nutrient use efficiency, yield and fiber quality in cotton, however, the performance of foliar applied nanofertilizers still requires improvement. Therefore, a two-year field experiment (2016-17 and 2018-19) was conducted at the Central Institute for Cotton Research, Regional Station, Coimbatore, to evaluate the effects of foliar application of different dosages of commercially available nanofertilizers, with and without surfactant, on cotton growth and yield. The ten treatments included T1-control, T2-recommended dose of fertilizer (RDF), T3-100 % Nualgi without surfactant, T4-200 % Nualgi without surfactant, T5-100 % Nualgi with surfactant, T6-200 % Nualgi with surfactant, T7-100 % Nanomol without surfactant, T8-200 % Nanomol without surfactant, T9-100 % Nanomol with surfactant and T10-200 % Nanomol with surfactant were replicated thrice and laid out in randomized block design (RBD). Nanofertilizers (T3-T10) were foliar sprayed at 45 and 90 days after sowing (DAS), i.e., at both vegetative and flowering stage of cotton (var. Suraj). The results revealed that the foliar application of Nualgi nanofertilizer with surfactant significantly increased nitrate reductase (NR) activity, total chlorophyll content, reducing sugar, total potassium content, the number of opened bolls per plant, boll weight and seed cotton yield. Similarly, foliar spraying of Nanomol nanofertilizer without surfactant significantly enhanced the reducing sugar, total nitrogen (N), number of opened bolls per plant, boll weight and seed cotton yield. On average, a 28 % increase in seed cotton yield was recorded with 100 % Nualgi nanofertilizer with surfactant (15.4 q ha-1) and 100 % of Nanomol nanofertilizer without surfactant (15.4 q ha-1) compared to RDF (12.0 q ha-1). However, fibre quality parameters were not significantly affected by the foliar application of nanofertilizers.